Visual Avoidance in Xenopus Tadpoles Is Correlated With the Maturation of Visual Responses in the Optic Tectum - Dong, Wei (American Physiological Society, 2009)
The optic tectum is central for transforming incoming visual input into orienting behavior. Yet it is not well understood how this behavior is organized early in development and how it relates to the response properties of the developing visual system. We designed a novel behavioral assay to study the development of visually guided behavior in Xenopus laevis tadpoles. We found that, during early development, visual avoidance—an innate, tectally mediated behavior—is tuned to a specific stimulus size and is sensitive to changes in contrast. Using in vivo recordings we found that developmental changes in the spatial tuning of visual avoidance are mirrored by changes in tectal receptive field sharpness and the temporal properties of subthreshold visual responses, whereas contrast sensitivity is affected by the gain of the visual response. We also show that long- and short-term perturbations of visual response properties predictably alter behavioral output. We conclude that our assay for visual avoidance is a useful functional measure of the developmental state of the tectal circuitry. We use this assay to show that the developing visual system is tuned to facilitate behavioral output and that the system can be modulated by neural activity, allowing it to adapt to environmental changes it encounters during development.